Drivers and impacts of evolving land access in Ghana’s cocoa landscapes - Doreen Asumang-Yeboah; Joana Akua Serwaa Ameyaw; Emmanuel Acheampong (African Journal on Land Policy and Geospatial Sciences)
Context and background